In vitro assessment of Bacillus subtilis FJ3 affirms its biocontrol and plant growth promoting potential - Jan, Faisal; Arshad, Hamza; Ahad, Mehreen; Jamal, Asif; Smith, Donald L. (Frontiers in Plant Science, 2023)
Bacillus species and their metabolites have potential alternative as chemical pesticides that can limit the growth of potential plant pathogens and enhance crop productivity. The aim of this study was to investigate the potential of Bacillus subtilis FJ3 for promoting plant growth and controlling fungal plant pathogens. The study evaluated the strain's ability to promote plant growth in vitro by characterizing its growth-promoting traits, which included the production of hydrolytic enzymes, indole acetic acid, siderophores, biofilm formation, and phosphate solubilization. PCR testing revealed that strain FJ3 has the potential to produce lipopeptides such as fengycin, surfactin, mycosubtilin, and pilpastatin. Through in vitro antagonism testing it was demonstrated that strain FJ3 is able to inhibit Fusarium oxysporum by 52% compared to the untreated control and was antagonistic against Aspergillus flavus, Aspergillus niger and Rhizopus oryzae using a dual method. Minimum inhibitory concentration of Bacillus crude extract resulted in 92, 90, 81.5 and 56% growth inhibition of Fusarium oxysporum, A. niger, A. flavus and Rhizopus oryzae, respectively. In FT-IR and GC-MS analysis of crude LPs extract, the transmission and mass spectrum confirmed the existence of aforesaid lipopeptides containing βfatty acids with chain length ranging from C14 to C21 in which the majority are saturated fatty acids. Greenhouse experimentation revealed that Bacillus strain FJ3 and its metabolites significantly diminished the disease incidence with an average reduction of 31.56%. In sterilized soil, FJ3 and its metabolites caused 24.01 and 10.46% growth promotion, respectively, in chickpea . The results demonstrated that Bacillus strain FJ3 has broad spectrum antifungal and plant growth promoting activities and could be a promising candidate for development into a commercialized biobased product for use in a sustainable agriculture practice.